Guided self-help interventions for irritable bowel syndrome. Issue 10 (October 2015) - Liegl, Gregor; Plessen, Constantin Y.; Leitner, Anton; Boeckle, Markus; Pieh, Christoph
<x xml:space="preserve">Abstract</x> Objective Although irritable bowel syndrome (IBS) is highly prevalent and is accompanied by high costs for respective healthcare systems, the data on treatment effectiveness are limited. Current treatment methods have limitations in terms of side effects and availability. Guided self-help (GSH) might be an easily accessible and cost-effective treatment alternative. This study is the first systematic review and meta-analysis of GSH interventions for IBS. Methods Using electronic databases (MEDLINE, SCOPUS, PsycINFO, and Web of Science), we performed a systematic search for randomized-controlled trials. Using a random-effect model, we calculated the pooled standardized mean differences (SMDs) of GSH on IBS symptom severity (primary outcome) and quality of life (secondary outcome). We additionally examined the moderating effects of online-based interventions and face-to-face therapist contact by applying mixed models. Results A systematic literature search identified 10 eligible randomized-controlled trials, including 886 participants. Compared with the control conditions, the effect size was medium for the decrease in IBS symptom severity (SMD=0.72; 95% confidence interval: 0.34–1.08) and large for the increase in patients' quality of life (SMD=0.84; 95% confidence interval: 0.46–1.22). Neither treatment format nor face-to-face contact was a predictor of therapy outcomes in between-group analyses. In contrast, within-group analyses led to the conclusion that online-based interventions are more effective than other self-help formats. Conclusion GSH is an effective alternative for the treatment of IBS. As GSH methods are easy to implement, it seems sensible to integrate GSH into clinical practice. Limitations With respect to the high study heterogeneity, the number of studies included was relatively small.